The association between cadmium exposure and lung cancer risk: A protocol for systematic review and meta-analysis - Lin Chen; Min Zhou; Dingliang Lv; Shuiwei Qiu (PLoS ONE, 2025)
Background Cadmium (Cd), a toxic heavy metal, is classified as a human carcinogen by the International Agency for Research on Cancer (IARC). Epidemiological studies suggested a potential link between cadmium exposure and lung cancer risk, but evidence has remained inconsistent, particularly regarding differences between occupational and general populations. This protocol will outline a systematic review and meta-analysis to quantify the association between cadmium exposure (via blood, urine, hair, or environmental samples) and lung cancer risk. Methods This study protocol will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols (PRISMA-P) guidelines. A comprehensive search of PubMed, Embase, Web of Science, Medline, and Cochrane databases will identify observational studies published from inception to December 2024. Two reviewers will independently screen studies, extract data, and assess the quality of included using the Newcastle-Ottawa Scale (NOS). We will harmonize data to calculate pooled relative risks (RRs) with 95% confidence intervals (CIs). Random-effects model is anticipated for high-heterogeneous results, while fixed-effects model will be adopted for low- heterogeneous results. Sub-group analyses (e.g., population type (general/occupational), geographic region, year of publication), sensitivity analyses, and assessments of publication bias (Egger’s test, funnel plots) will be conducted to ensure the robustness and reliability of the findings. The analyses will be conducted via RevMan 5.3 and STATA 15 software. Discussion This protocol will guide the standard process of the systematic review, providing synthesized evidence on the short-, and long-term effect of cadmium on lung risk in general and occupational populations. Conclusion This systematic review and meta-analysis will provide synthesized evidence regarding cadmium exposure with lung cancer risk in both occupational and general populations. The evidence obtained in this study can inform the public and the policy-making bodies. Register on PROSPERO CRD42024527248.